Intraarticular Morphine and Bupivacaine Reduces Postoperative Pain After Rotator Cuff Repair. Issue 6 (1st November 2000) - Tetzlaff, John E.; Brems, John; Dilger, John
Abstract : Background and Objectives: To determine whether intraarticular injection of morphine, fentanyl, or sufentanil added to bupivacaine provided pain control after open rotator cuff repair. Methods: These data were collected as a prospective, randomized, blinded observer study. All patients received a standard interscalene anesthetic with 1.4% mepivacaine with 1:200, 000 epinephrine. At the conclusion of surgery, they received an intraarticular injection after the shoulder capsule was closed. Patients were randomized into 4 groups. All received 20 mL of 0.25% bupivacaine: group 1, plain; group 2, with 1 mg of morphine added; group 3, with 50 μ g of fentanyl added; and group 4, with 10 μ g of sufentanil added. Pain scores in the postanesthesia care unit were evaluated at 0, 30, 60, 90, 120, and 240 minutes and at 4-hour intervals postoperatively using a visual analogue scale. Breakthrough pain was managed with morphine, via patient controlled analgesia pump. Results: Thirty-nine patients were entered into the study. Pain scores at 2 hours and beyond were lowest in group 2. Total morphine utilization was significantly lower for the first 24 hours in group 2. Conclusions: Intraarticular injection of the shoulder with 0.25% bupivacaine and 1 mg morphine at the conclusion of surgery provided pain control and diminished morphine used in the first 24 hours after open rotator cuff repair. Fentanyl and sufentanil did not improve the analgesia over that achieved with bupivacaine alone.